2022
DOI: 10.3390/jof8121236
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Fungal Diseases in Africa: A Critical Literature Review

Abstract: Invasive fungal diseases (IFDs) are of huge concern in resource-limited settings, particularly in Africa, due to the unavailability of diagnostic armamentarium for IFDs, thus making definitive diagnosis challenging. IFDs have non-specific systemic manifestations overlapping with more frequent illnesses, such as tuberculosis, HIV, and HIV-related opportunistic infections and malignancies. Consequently, IFDs are often undiagnosed or misdiagnosed. We critically reviewed the available literature on IFDs in Africa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 232 publications
0
12
1
Order By: Relevance
“…Besides invasive candidiasis, this finding is consistent with previous studies of other invasive fungal infections, including pulmonary aspergillosis. 26 , 89 91 Consequently, male sex has also been shown to be significantly associated with mortality, although this was not significant in our study. Besides underlying comorbidities and behavioural risk factors, there may exist the role of genetics and gender-specific immunological differences that may render males more susceptible, which necessitates further research studies into the mechanisms.…”
Section: Discussioncontrasting
confidence: 77%
“…Besides invasive candidiasis, this finding is consistent with previous studies of other invasive fungal infections, including pulmonary aspergillosis. 26 , 89 91 Consequently, male sex has also been shown to be significantly associated with mortality, although this was not significant in our study. Besides underlying comorbidities and behavioural risk factors, there may exist the role of genetics and gender-specific immunological differences that may render males more susceptible, which necessitates further research studies into the mechanisms.…”
Section: Discussioncontrasting
confidence: 77%
“…We used an estimate of candidemia rate of 5/100,000 population, probably a conservative estimate based on other resource-constrained countries. 53 , 54 Many will be undiagnosed as blood cultures are only done in major hospitals, 73 , 74 and in any case are only ~40% sensitive for invasive candidiasis. Without local data, we cannot summarize the species distribution of Candida and other yeasts in bloodstream infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of awareness and training among the physicians and laboratory personnel is probably the main reasons for under-reporting and under recognition of cases. Of note that CM, PCP, and histoplasmosis are increasingly reported in Africa [ 104 , 105 ]. A recent study from Nigeria found that 7.7% of HIV patients with low CD4 counts tested positive for Histoplasma antigen [ 104 ].…”
Section: Discussionmentioning
confidence: 99%